Lessons From the Trenches: Students’ Perspectives of Their Own Marine Transdisciplinary Education - Wilson, Megan N.; Laufer, Adrian E.; Howard, Erin M.; Wong-Ala, Jennifer A. T. K. (Frontiers in Marine Science, 2021)
Recent environmental changes have demonstrated that the Earth has entered the Anthropocene. In this new age, complex interactions between human and natural systems exacerbate “wicked problems” that challenge researchers to engage both deep disciplinary expertise and broad integrative knowledge to address these societally relevant problems. Researchers and practitioners are making an increased effort to bridge the divide between human and natural systems research by facilitating multi-, inter-, and transdisciplinary collaborations. Despite 21st century changes to the research environment, the structure of a typical graduate education remains largely unchanged over the past several decades. Wicked problems necessitate communication and collaboration expertise; innovative transdisciplinary training and research opportunities can equip graduate students with these necessary skills. Oregon State University has offered such an opportunity through an NSF-funded Research Traineeship Program (NRT) for students focusing on Risk and Uncertainty Quantification and Communication in Marine Science. Herein, we reflect on the experience of graduate students who successfully completed the NRT and assert that support for transdisciplinary training and research at the graduate stage is urgently needed. We present five lessons learned from our year-long transdisciplinary project focused on the development of an approach for integrating diverse data sets within a social-ecological systems framework to reach a broader understanding of the interconnections between a marine reserve system, people, and the environment. Finally, we present current challenges and paths forward to enhance the success of early career transdisciplinary research.